Imaginary Friends - González Caparrós, Claudia (Barcelona : Fundació Joan Miró, 2023)
Pivi, Paola ; Bosmans, Kasper ; Apfelbaum, Polly ; Miró, Joan ; Gaba, Meschac ; Eisma, Afra ; Rist, Pipilotti ; Creed, Martin ; Wurm, Erwin ; Hein, Jeppe
Imaginary Friends, Fundació Joan Miró, Barcelona, 16 March to 2 July 2023
boek